The Failure of the Mass Media to Construct the Communities in Ledok Wetan and Sumbangtimun Villages, Bojonegoro Regency, Related to the Flood Problem of Bengawan Solo - mondry, mondry (Advances in Social Sciences Research Journal, 2019)
The mass media is often informed of successfully constructing communities. Many books and journals have written about the success of mass media in constructing the communities. This study, however, examines how the mass media failed to construct the communities of Ledok Wetan and Sumbangtimun Villages, Bojonegoro Regency, East Java, Indonesia in the case of Bengawan Solo floods. The failure was not due to the failure of Berger and Luckmann’s theory (2012) of the construction of social reality, but because the communities considered that floods from the longest river in Java were not harmful to human life and not economically harmful. Because of this assessment, the public does not feel worried about doing harmful things, such as throwing garbage into Bengawan Solo. At the same time, the mass media also did not assess the Bengawan Solo floods that occur every rainy season every year, go through 3 cities and 17 districts, and involve thousands of refugees as a serious problem. National mass media did not report the flood problem of Bengawan Solo, while the local media only reported when the flood occurred, between two to seven days. There is no news that aims to inform, educate, and influence the community to better anticipate the floods of the Bengawan Solo, to minimize their impact. In fact, newspapers distributed in the flood victims’ communities do not report about flood news. Keywords: Failure, Mass Media, Construction, Flooding, Bengawan Solo River